Relationships, Human Nature, and the Four "Words" of Inspector Gamache1. Issue 2 (June 2017) - Largen, Kristin Johnston
Abstract: The Inspector Gamache mysteries by Louise Penny are very popular, in no small part because of the appeal of the main character, Chief Inspector Armand Gamache. However, another main draw of the series is the small set of recurring main characters. In this article, I delve deeply into their lives and relationships, using as a lens the four sayings of Gamache as a means of illuminating both the brokenness and grace that characterize human relationality.